CONCEPTUAL CONSIDERATIONS ABOUT MALE SUBJECTIVITY TO THE REALM OF FEEDING AND NUTRITION - Roberto Carvalho Alves Filho; Francisco Romão Ferreira; Cristiane Marques Seixas; Fabiana Bom Kraemer (Universidade do Estado do Rio de Janeiro, 2016)
This essay presents some reflections produced in the course of writing the master thesis entitled "Health in the human body: the construction of subjectivity about the male body in Men's Health magazine." We present some concepts and theoretical references used in the thesis and we consider this essay as the first articulation between the discussions about gender, health, feeding and consumption. We intend to present a mosaic of issues based on Howard Becker's perspective (1994), to whom the mosaic image is useful because each piece added contributes to some extent to the knowledge of the whole picture. Thus, the different theoretical fragments joined here arrange the mosaic and contribute differently to our knowledge about how food, different masculinities, health care and the discourses of science, the media and the market articulate themselves in the meaning of "human health," thus bringing forth new subjectivities attached to the consumption of ideal models of body and health. DOI: 10.12957/demetra.2016.22485